Metaphor Analysis on Color Lexicon with Plant Attributes in Madurese Language - Fadhilah, Nurul; Rais, Wakit Abdullah; Purnanto, Dwi (Lingua Cultura, 2019)
The research aimed to describe the Madurese color lexicons with plant attributes and to analyze those lexicons metaphorically.Â This research engaged 18 informants to denote Madurese color lexicons by showing 139 color cards. The referentialÂ comparison method was followed by sorting the decisive element technique through referential competence-in-dividing, andÂ Connect Compare Equate as the advanced technique was used as the data analysis method. The research finds that 53 colorÂ lexicons with plant attributes in 8 Madurese color lexicons, namely potÑ â€˜whiteâ€™, celleng â€˜blackâ€™, mÑra â€˜redâ€™, bhiru â€˜greenâ€™,Â konÑng â€˜yellowâ€™, cokklat â€˜brownâ€™, bhiru â€˜blueâ€™, and bungo â€˜purpleâ€™. Furthermore, these plant attributes can be classified intoÂ fruits, flowers, vegetables, seeds, spices, leaves, trees, part of the tree, and part of the fruit. The domination of plant attributesÂ in Madurese color lexicons emerges due to the sociocultural factors embodied in Madurese ethnic group itself, those are (1)Â farming is Madurese main way of living, (2) Madurese ethnic group respect the nature as the place where they can pray andÂ thank God, and (3) some objects associated with color lexicons are abundantly available at their surroundings, thus theyÂ frequently use it in their daily life.